Knowledge, Attitudes, and Practices on Urinary Schistosomiasis among Primary Schoolchildren in Nelson Mandela Bay, South Africa - Sydlynn Dorné Hambury; Anna D. Grobler; Paula Ezinne Melariri (Journal of Parasitology Research)
Background. Schistosomiasis remains a public health concern in South Africa (SA), with the highest prevalence of infection found among schoolchildren under the age of 15 years. Knowledge, attitude, and practices (KAP) studies on schistosomiasis among schoolchildren under the age of 15 years are lacking in the study area. The study therefore assessed primary schoolchildren in Grades 4–7 to determine their knowledge regarding schistosomiasis in the various ages represented in these grades. Methods. The study employed a quantitative descriptive, cross-sectional survey research design approach. A structured, close-ended, Likert-scale, self-administered questionnaire was used to collect data from 458 learners in Grades 4 to 7 aged from 9 to 16 years. Data were analysed using Statistica version 13 software. Bivariate and multivariate techniques were further used to analyse and describe the data and significant associations at p=0.05 were further interrogated using Cohen’s d and Cramér’s V, to determine the practical significance. Results. Of the 458 learners who completed the questionnaire, 248 (54%) acknowledged having heard of schistosomiasis previously. There was a positive correlation between knowledge and attitude (0.779). The KAP scores were calculated as a percentage ranging between 0% and 100%, and this range was split into five equal width intervals 0–19%, 20–39%, 40–60%, 61–80%, and 81–100%. For knowledge, 210 (46%) of the participants obtained a score in the interval 0–19%. For attitudes, 237 (52%) of the participants obtained a score in the interval 0–19%. Therefore, the overall knowledge and attitudes among the study participants towards schistosomiasis were poor. There was a significant difference (p=0.0005, V=0.42 medium) between male and female participants relating to their practices. It was observed that a high percentage, 69 (15%) of males reported to swimming in slow-moving water compared to a significantly lower percentage, 9 (5%) of females. Furthermore, 23% of the participants reported that there was a river on the way to school. Conclusion. The study revealed that there was a positive correlation between knowledge and attitude. The overall knowledge and attitudes on schistosomiasis were poor. Furthermore, a gender-related difference based on practices emerged significant in the study. The findings are thus valuable in designing effective and targeted schistosomiasis control programmes.